A new stress-damage-flow coupling model and the damage characterization of raw coal under loading and unloading conditions. (February 2021) - Jiang, Changbao; Yang, Yang; Wei, Wenhui; Duan, Minke; Yu, Tang
Abstract: Coalbed methane, as a gas in coal seam, is a kind of potential clean energy with high reserves. At present, there are two main types of coalbed methane extraction in China, one is extracting coalbed methane by ground drilling, the other is coal and gas (coalbed methane) simultaneous extraction in coal mine underground. In the process of coal and gas simultaneous extraction, the migration of gas may not only cause coal and gas outburst, gas gushing and other disasters, but also cause the greenhouse effect. Therefore, in order to achieve the goal of safe simultaneous extraction of coal and gas and reducing greenhouse gas emissions, it is particularly important to understand the flow properties of gas and the damage characteristics of raw coal in the process of coal seam mining. In this paper, the mechanical properties and seepage characteristics of raw coal samples under loading and unloading conditions are studied experimentally by using the laboratory-fabricated 'thermal-hydro-mechanical coupled with triaxial servo controlled seepage apparatus for gas-containing coal'. At the same time, X-ray tomography is carried out on the raw coal samples before and after the experiment. The deformation, damage and seepage characteristics of raw coal samples in the experimental process are recorded and analyzed. On the basis of the above, based on the information entropy theory, the change rate of information entropy is proposed as a damage characterization parameter, and its feasibility is verified by the comparison and analysis with the change rate of porosity. Finally, according to the basic definition of porosity, combined with statistical damage model, considering the gas adsorption expansion and Klinkenberg effect, the evolution model of permeability under loading and unloading conditions is developed. The model can better reflect the permeability evolution law of raw coal under loading and unloading conditions.